2022
DOI: 10.3390/reprodmed3010006
|View full text |Cite
|
Sign up to set email alerts
|

Placental Maternal Vascular Malperfusion Is Associated with Prepregnancy and Early Pregnancy Maternal Cardiovascular and Thrombotic Profiles

Abstract: Characteristics of maternal vascular malperfusion (MVM) are frequently observed in placentas from pregnancies impacted by preeclampsia, intrauterine growth restriction, preterm labor, and intrauterine fetal demise. We sought to evaluate the associations of features of MVM with subclinical measures of cardiovascular health and coagulation potential in healthy young women. Sixty-three healthy young women were recruited and assessed prior to pregnancy on cycle day 9 ± 4, at gestational age 90 ± 6 of early pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Low TPVR (<1048 dyne s cm -5 ), high CO and eccentric hypertrophy of the LV relate to late complications. 4,97 Pre-conceptional hemodynamic assessment identifies chronic hypertension at risk for complications. The risk of recurrent PE and FGR relates inversely and linearly to preconception plasma volume (8% difference between women who will develop PE and controls).…”
Section: A Identification Of Women At Risk For Complication In Pregnancymentioning
confidence: 99%
See 3 more Smart Citations
“…Low TPVR (<1048 dyne s cm -5 ), high CO and eccentric hypertrophy of the LV relate to late complications. 4,97 Pre-conceptional hemodynamic assessment identifies chronic hypertension at risk for complications. The risk of recurrent PE and FGR relates inversely and linearly to preconception plasma volume (8% difference between women who will develop PE and controls).…”
Section: A Identification Of Women At Risk For Complication In Pregnancymentioning
confidence: 99%
“…Low TPVR (<1,048 dyne•s•cm À5 ), high CO, and eccentric hypertrophy of the LV relate to late complications. 4,97 Preconceptional hemodynamic assessment identifies chronic hypertension at risk for complications.…”
Section: The Hemodynamic Status Of the Woman During The Preconception...mentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21] We previously showed that pregnancy was protective of ischemic brain injury and associated with high ischemic tolerance, an effect prevented in a model of PE. 22 While it is known that circulating levels of prothrombin and thrombin are elevated in pregnancy and further heightened in PE, which may increase the risk of stroke, 3,12,23,24 it is largely unknown if thrombin levels and PAR expression in the brain and cerebral vasculature are affected, which may impact stroke outcomes. In addition, exogenous thrombin has been shown to have a role in hemodynamic recovery in response to ischemia by promoting both arteriogenesis and angiogenesis in noncerebral vessels.…”
Section: Introductionmentioning
confidence: 99%